A Case of Thoracoabdominal Open Conversion after EVAR with Type V Endoleak - Amako, Mau; Hayama, Masato; Wada, Hideichi; Suzuki, Hiroyuki; Matsumura, Hitoshi (Japanese Journal of Vascular Surgery, 2020)
The case, 76-year-old man underwent endovascular aneurysm repair (EVAR) for abdominal aortic aneurysm with maximum diameter of 75 mm 4 years ago. The patient was referred to our hospital for back pain, anemia and gastrointestinal bleeding. CT showed an enlarged abdominal aortic aneurysm with maximum diameter 90 mm, and no endoleak. An urgent surgical repair was performed using thoracoabdominal aortic aneurysm surgery approach. The aneurysm sac was found to be filled with gelatinous material without evidence of thrombus or active bleeding, so we diagnosed enlargement of the aneurysm as Type V endoleak. The postoperative course was uneventful and there was no particular problem with postoperative CT. Thoracoabdominal approach provides good surgical fields and is very useful to control proximal aorta in cases of open conversion after EVAR.